2020
DOI: 10.1111/1471-0528.16562
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya infection in pregnancy – reassuring maternal and perinatal outcomes: a retrospective observational study

Abstract: Objective To evaluate pregnancy and neonatal outcomes, disease severity, and mother‐to‐child transmission of pregnant women with Chikungunya infection (CHIKV). Design Retrospective observational study. Setting Grenada. Population Women who gave birth during a Chikungunya outbreak between January 2014 and September 2015 were eligible. Methods This descriptive study investigated 731 mother‐infant pairs who gave birth during a CHIKV outbreak. Women and infants underwent serological testing for CHIKV by ELISA. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Similar results were found by Foeller in Grenada (August-December 2014); however, they found intense arthralgia and myalgia but with shorter durations in women who became infected with CHIKV during gestation [131]. Both authors found that the frequency of newborns who need intensive care unit admission seems to be higher when the women are exposed to CHIKV within 1 week before delivery, as well as pregnancy complications [130,131]. In contrast, a study conducted in India between August and October 2016 enrolled 150 CHIKV-infected pregnant women with a mean period of gestation of 25.62 ± 13.475 weeks.…”
Section: Vertical Transmission In Chikungunyasupporting
confidence: 87%
“…Similar results were found by Foeller in Grenada (August-December 2014); however, they found intense arthralgia and myalgia but with shorter durations in women who became infected with CHIKV during gestation [131]. Both authors found that the frequency of newborns who need intensive care unit admission seems to be higher when the women are exposed to CHIKV within 1 week before delivery, as well as pregnancy complications [130,131]. In contrast, a study conducted in India between August and October 2016 enrolled 150 CHIKV-infected pregnant women with a mean period of gestation of 25.62 ± 13.475 weeks.…”
Section: Vertical Transmission In Chikungunyasupporting
confidence: 87%
“…Similarly, the detection of IgG antibodies in newborn could be suggestive of transplacental antibody transfer from mothers during pregnancy, as found in some studies [ 41 , 42 ]. This finding further suggests exposure in women of childbearing age, which could have harmful effects on their babies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal and perinatal CHIKV infection has been associated with various clinical outcomes ( Ferreira et al , 2021 ). Some studies suggest minimal risk due to perinatal CHIKV infection, but small numbers of cases with severe outcomes including death advocate for systematic research on pregnancy outcomes in the context of CHIKV infection ( Ferreira et al , 2021 ;Escobar et al, 2017 ;Fritel et al, 2010 ;Foeller et al, 2021 ;. For three major ABV, the problems are exacerbated by challenges in access and equity in maternal-child health services ( Rodriguez-Morales et al, 2018 ;Tepper et al, 2016 ) and a lack of countermeasures such as antivirals and vaccines approved for use in pregnancy.…”
Section: Introductionmentioning
confidence: 99%